2005
DOI: 10.1021/om0490031
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of C2B4Carborane Chemistry:  from Early Years to the Present

Abstract: A review of the chemistry of polyhedral cluster complexes in which s-, p-, d- and f-block metals are incorporated mainly into C cage -trimethylsilyl-substituted C2B4 carborane cages is presented. While the main thrust of this review is on the results obtained in authors' laboratories, comparisons are made to similar systems and to those involving both large- and small-cage carboranes. In this way we hope to demonstrate the unique chemistry of the small-C2B4-cage systems that has emerged over the last 40 years.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(19 citation statements)
references
References 306 publications
0
19
0
Order By: Relevance
“…Herein we describe the syntheses, structures and detailed bulk and spectroscopic studies of the electronic properties of homoleptic, zwitterionic 2 ] complexes. In addition, some density functional theory (DFT) studies have been used to support the findings of the presented experimental results.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Herein we describe the syntheses, structures and detailed bulk and spectroscopic studies of the electronic properties of homoleptic, zwitterionic 2 ] complexes. In addition, some density functional theory (DFT) studies have been used to support the findings of the presented experimental results.…”
Section: Resultsmentioning
confidence: 99%
“…So far, only the Au I compounds have been shown to be coordinated by the apical carbanion of R Tpmd to form a linear, two-coordinate complex containing a covalent AuÀC bond. [13,16] Since no homoleptic transition metal sandwich complex of the general formula [MA C H T U N G T R E N N U N G ( R Tpmd) 2 ] has been reported until now, it was of interest to check the accessibility, structure and electronic characteristics of such compounds and to compare them with the corresponding Tp R or R Tpm complexes. Previously, we concluded that k 3 N-Tp R and k 3 N-…”
Section: Methanides [Ca C H T U N G T R E N N U N G (R 2 Pz) 3 ]mentioning
confidence: 99%
See 3 more Smart Citations